2023
DOI: 10.1039/d3fo04051h
|View full text |Cite
|
Sign up to set email alerts
|

Akkermansia muciniphilaattenuated lipopolysaccharide-induced acute lung injury by modulating the gut microbiota and SCFAs in mice

Jian Shen,
Shuting Wang,
He Xia
et al.

Abstract: Akkermansia muciniphila attenuated lipopolysaccharide-induced acute lung injury by modulating the gut microbiota and SCFAs in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…However, the MPTP + Akk treatment significantly decreased the C S /C F of isobutyric acid and isovaleric acid compared to the MPTP + Vehicle group. Taken together, these results suggest that Akk treatment led to a reduction in intestinal permeability in PD mice to some extent, which is consistent with previous research suggesting that Akk improves intestinal barrier function [9,11,21].…”
Section: Akk Treatment Regulated Production Of Serum and Fecal Scfas ...supporting
confidence: 92%
See 1 more Smart Citation
“…However, the MPTP + Akk treatment significantly decreased the C S /C F of isobutyric acid and isovaleric acid compared to the MPTP + Vehicle group. Taken together, these results suggest that Akk treatment led to a reduction in intestinal permeability in PD mice to some extent, which is consistent with previous research suggesting that Akk improves intestinal barrier function [9,11,21].…”
Section: Akk Treatment Regulated Production Of Serum and Fecal Scfas ...supporting
confidence: 92%
“…In the present study, we also investigated the role of Akk in neurogenesis. As for the mechanisms of Akk, it has been reported that it may exert beneficial effects on the host through its major metabolites, which are short-chain fatty acids (SCFAs) [ 20 , 21 ]. Another study demonstrated that decreased SCFAs in feces and increased SCFAs in plasma in PD patients correlated with specific alterations in the gut microbiota and the extent of PD clinical severity [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Akkermansia muciniphila is a promising candidate probiotic that has beneficial effects on host immunologic and metabolic functions [ 48 ]. The causal evidence of its anti-inflammatory property via reducing the levels of inflammatory cytokines has been reported in a variety of mouse model studies [ 49 , 50 ]. On the other hand, the close intra-system interactions indicated that our findings were reliable, such as that slaughter weight was intimately associated with carcass weight and the different stress status indicators were positively or negatively correlated with production performance.…”
Section: Discussionmentioning
confidence: 99%
“…A. muciniphila has the function of reducing FFA levels by alleviating obesity. In addition, A. muciniphila improved the structure and composition of the intestinal microbiota and promoted the production of short-chain fatty acid ( 88 ). Acetic acid, propionic acid and butyric acid targeted G protein-coupled receptors 41 and 43 on the surface of intestinal L cells, which activated downstream molecular signaling and ultimately promoted the secretion of glucagon-like peptide-1(GLP-1) ( 89 ).…”
Section: The Utility Of a Muciniphila In Metabolic...mentioning
confidence: 99%